Microwave-assisted synthesis of mesoporous silica nanoparticles as a drug delivery vehicle - Kamarudin, N. H. N. (Malaysian Society of Analytical Sciences, 2016)
Nanotechnology has been utilized in medicine for therapeutic drug delivery and the development of treatments for a variety of diseases and disorders. Mesoporous silica nanoparticles (MSN), which combine both unique properties of nanomaterials and mesostructured substances, have aroused special attention in biomedical research field due to its great advantages in many aspects such as well biocompatible, unique properties of tunable pore size and structure, large surface areas and pore volumes, controllable morphology and modifiable surfaces, high chemical and thermal stabilities. In this study, the microwave was utilized to synthesize MSN under 100 W, 300 W and 450 W heating powers. All MSNs was tested for adsorption and release of an anti-inflammatory and anti-cancer drug, ibuprofen. The characterization revealed that the MSN prepared under 450 W (MSN450) produced the most ordered and prominent mesoporous structure compared to lower power applied. MSN450 exhibited the highest ibuprofen adsorption, followed by MSN300 and MSN100, confirming that more ordered MSN demonstrated higher adsorptivity toward ibuprofen. For the release study, MSN450 showed the slowest release rate of ibuprofen, followed by MSN300 and MSN100. All MSNs was found to exhibit good activity for the ibuprofen adsorption and release.